Igbo Culture and Business Practices in South East Nigeria: A Critical Review - I. Idemobi, Ellis; N. Okafor, Chisom; N. Dike, Goodfaith; I. Anyika, Michael (British Journal of Marketing Studies, 2024)
This study examined the relationship between Igbo culture and business practices in the South-Eastern region of Nigeria. Over the years, scholars have introduced so many leadership, management and business theories to guide businesses. This study aims to examine critical Igbo cultural practices that serve same purposes as some of these business management theories in guiding business successes in the South East of Nigeria. This study also looked at how the Igbo culture and Igbo leadership influence Igbo entrepreneurial practices. It was found that so many Igbo Cultural practices such as Igbo apprenticeship system and business mentorship guide and motivate Igbo entrepreneurs to succeed in business. As a result of these values, individuals train under their master to gain general business management skills (known as Igba-Boi). In some cases, some of trainees end up pursuing other types of businesses quite different from the where they served using the same business skills in the new trades. The study recommended that Nigerian government should learn from western government in encouraging Igbo apprenticeship system that governs most successful businesses among Ndigbo and developed as an official business incubation system for the youth. The study further recommended government can support individuals who have mastered certain skills but lack capital with fund infusion.